Особенности магнитно-импульсной обработки металлов в технологиях современности - Батыгин, Ю.В.; Гнатов, А.В.; Гнатова, Щ.В.; Степанов, А.А.; Чаплыгин, Е.А. (Електротехніка і електромеханіка, 2011)
In the article the analysis of the magnetic pulse metal working features in the modern technologies is conducted. The hyperplasticity effect essence is exposed and its particularities are analysed. A thin-walled metal condition during magnetic pulse action is formulated.